Implementasi Penggunaan Gadget yang Bijak dengan Melibatkan Peran Orang Tua di Desa Sirnaresmi - Syifa Aqmaliyah; Rizki Amelia; Ikhsan Fauzi Hanafiah; Nur Arif Muhhammad (Universitas 45 Surabaya, 2025)
Technological advancement has significantly influenced parenting patterns, including in Sirnaresmi Village, Gunung Guruh District, Sukabumi Regency. Many children use gadgets primarily for entertainment without adequate supervision, making them vulnerable to addiction and exposure to inappropriate content. This community service program aimed to improve mothers’ understanding of how to guide their children in using gadgets safely and productively. The activity employed a participatory socialization method through interactive lectures, group discussions, Q&A sessions, and simple simulations. An evaluation was conducted using pre-test and post-test assessments to measure changes in participants’ knowledge.The results indicated a considerable improvement in three key aspects: parental guidance, internet ethics and safety, and strategies for managing screen time and selecting appropriate content. The average score for parental guidance increased from 48 to 82 (70%), internet ethics and safety from 46 to 72 (56%), and screen-time and content-management strategies from 44 to 75 (70%). This program was considered moderately successful because the concise, practical material encouraged active participation, despite time constraints and minor technical issues.